Programming Languages and Systems: 27th European Symposium on Programming, ESOP 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings - Ahmed, Amal (Theoretical Computer Science and General Issues Series, 2018)
artificial intelligence; computer architecture; computer software selection and evaluation; distributed computer systems; formal logic; formal model; java; model checking; processors; program compilers; program verification; programming language; semantics; separation logic; software engineering specifications; theorem proving; type; systems verification